Pleasure of body, order of mind. Kantian remarks about the contemporary theory of emotions - Ferrara, Ilaria (Aesthetica Preprint, 2023)
This paper aims to focus on a Kantian “emotional consciousness”, connected to the aesthetic and affective subjectivity exposed in the Critique of Judgment and related to some issues concerning contemporary theories of emotions. This essay will try to valorise Kantian anthropological emotions [Affekten], that “prepare” the treatment of the pleasure of beauty as a free game through a homeostatic balance of bodily sensations. The first part will analyse the concept of Kantian animus, seeing how the Kantian perspective on regulative and evaluative emotions offers suggestions on the appraisal theory. The second part will try to connect Kantian sensible pleasure with some theories of emotion embodied in contemporary enactivism. The last part of the paper, starting from the concept of pleasure as a specific mental activity, will deepen the Kantian conception of “emotional causality” as an essential point of interest for the debate in the contemporary philosophy of emotions, between cognitivism and affectivism.